Rinas real estate enterprise: property agents / Muhammad Azim Aziz... [et al.] - Aziz, Muhammad Azim; Lukman, Muhammad Ismail; Sarmidi, Muhammad Rofiqi; Abd Rahman, Nabilah Nor; Sazali, Muhammad Syazrul Ezree (2013)
Rinas Real Estate Enterprise is a new partnership company that act as property agents which provides advise,consult and to assist our customer to buy their dream house.